Modernity and Gender: A Critique of Modernization Theory - Luintel, Youba Raj (Himalayan Journal of Sociology and Anthropology, 2014)
This paper provides a bold critique of the hegemonic dualism in the light of insights that Tariq Banuri has offered. It also demonstrates the contours of gender asymmetry as an outcome of the masculine impersonal map of modernization. Highlighting the alternative model of development, it seeks to see the implication it has in the context of gender. The first section introduces the context with some of the questions to be focused on. It follows by a discourse of modernization and by an appraisal of Banuri’s main arguments on cultural maps and knowledge hierarchy. Conceptual contours of modernization and gender are sought before the final section puts forward empowerment as an alternative thesis. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10732 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 221-235